Earths Are Not Super-Earths, Saturns Are Not Jupiters: Imprints of Pressure-bump Planet Formation on Planetary Architectures - Wenrui Xu; Songhu Wang (The Astrophysical Journal Letters, 2024)
In protoplanetary disks, sufficiently massive planets excite pressure bumps, which can then be preferred locations for forming new planet cores. We discuss how this loop may affect the architecture of multiplanet systems and compare our predictions with observations. Our main prediction is that low-mass planets and giant planets can each be divided into two subpopulations with different levels of mass uniformity. Low-mass planets that can and cannot reach the pebble isolation mass (the minimum mass required to produce a pressure bump) develop into intra-system similarity “super-Earths” and more diverse “Earths,” respectively. Gas giants that do and do not accrete envelopes quickly develop into similar “Jupiters” and more diverse “Saturns,” respectively. Super-Earths prefer to form long chains via repeated pressure-bump planet formation, while Jupiter formation is usually terminated at pairs or triplets due to dynamical instability. These predictions are broadly consistent with observations. In particular, we discover a previously overlooked mass uniformity dichotomy among the observed populations of both low-mass planets (Earths versus super-Earths) and gas giants (Saturns versus Jupiters). For low-mass planets, planets well below the pebble isolation mass (≲3 M _⊕ or ≲1.5 R _⊕ for Sun-like stars) show significantly higher intra-system pairwise mass differences than planets around the pebble isolation mass. For gas giants, the period ratios of intra-system pairs show a bimodal distribution, which can be interpreted as two subpopulations with different levels of mass uniformity. These findings suggest that pressure-bump planet formation could be an important ingredient in shaping planetary architectures.